2020
DOI: 10.3390/ijerph17249403
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue and Endocrine-Disrupting Chemicals: Does Sex Matter?

Abstract: Obesity and metabolic-related diseases, among which diabetes, are prominent public health challenges of the 21st century. It is now well acknowledged that pollutants are a part of the equation, especially endocrine-disrupting chemicals (EDCs) that interfere with the hormonal aspect. The aim of the review is to focus on adipose tissue, a central regulator of energy balance and metabolic homeostasis, and to highlight the significant differences in the endocrine and metabolic aspects of adipose tissue between mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 221 publications
(173 reference statements)
1
20
0
2
Order By: Relevance
“…Expecting individuals to take responsibility for reducing exposure is unlikely to be a sufficient policy response. 48 The second approach from the scientific reviews is to develop clinical treatments for counteracting the effects of EDCs, by reducing the toxic effects or eliminating the EDCs from the body. Susceptible individuals may be identified through genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Expecting individuals to take responsibility for reducing exposure is unlikely to be a sufficient policy response. 48 The second approach from the scientific reviews is to develop clinical treatments for counteracting the effects of EDCs, by reducing the toxic effects or eliminating the EDCs from the body. Susceptible individuals may be identified through genomic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissues, which also express AHR but not PXR and CAR (Ref. in [5]) were investigated and Ahr mRNA levels fluctuated negatively with estrogens in the SAT as observed in the liver, while no significant effect was described in the VAT samples (Figure S2). It indicated that xenobiotic receptors were transcriptionally regulated in a distinct way depending on metabolic tissues.…”
Section: Impact Of Estrogen Withdrawal/replacement and Pollutant Mixture On The Expression Of Xenobiotic Processing Genesmentioning
confidence: 99%
“…According to the World Health Organization [1], there are around 2 billion adults overweight, of those 650 million are considered to be affected by obesity (BMI ≥ 30 kg/m 2 ). Obesity and metabolic diseases reflect an energy imbalance of multifactorial causes, including an environmental origin, according to convincing epidemiological data and experimental studies [2][3][4][5]. Endocrine disruptors are of particular concern since they can interfere with any hormonal action at low doses with non-monotonic dose-response curves [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, whole-body MR knockout mice have reduced fat mass and body weight [18]. It is estimated that there is sexual dimorphism in MR expression in humans, and its expression could be suppressed by the female biological clock [19]. However, more research is needed to determine how MR expression is affected by sex.…”
Section: Introductionmentioning
confidence: 99%